Microstructure-based non-Fourier heat transfer modeling of HIFU treatment for thyroid cancer. (December 2020) - Namakshenas, Pouya; Mojra, Afsaneh
Highlights: The thermal effect of blood vessels is taken into account during the HIFU modeling. Non-Fourier heat transfer is modeled by considering two time delays. Time delays are linked with the parameters of vascular region. Convective heat transfer is modeled between vascular and extravascular regions. Thermal energy is obtained from non-linear acoustic waves with 4 excited harmonics. Abstract: Background and objectives: High intensity focused ultrasound is an emerging non-invasive technique for the thermal ablation of cancer. Modeling of high intensity focused ultrasound as a method to induce hyperthermia, by considering non-equilibrium convective heat transfer has been under-represented in the previous studies. Therefore, in the present study, we aimed to study the effect of blood vessels during high intensity focused ultrasound ablation of thyroid cancer. In addition, high intensity focused ultrasound modeling was greatly improved by considering non-Fourier heat transfer. Methods: The modified dual-phase-lag model was used for the modeling of heat transfer in thyroid cancer during the ultrasound irradiation. The model parameters were linked with the tissue's microstructure parameters. Meanwhile, an interfacial convective heat transfer was considered between the blood vessels and the extravascular matrix. The extent of the vascular region was determined using the field emission scanning electron microscopy images. The non-linear Westervelt equation was solved for the sound wave to determine the heat source for the induced hyperthermia treatment. Results: Referring to the acoustic results, sharp-wave ripples were observed due to the inclusion of notable amplitudes of excited harmonics. The thermal results showed a maximum temperature rise of 25.08°C and 51.47°C at the powers of 5 W and 10 W using the modified dual-phase-lag model, while the Pennes model predicted a temperature rise of 28.77°C and 55.5°C at the same powers. It was also concluded that a constant blood temperature, overestimates the dissipated energy and the temperature reduction during the cooling period, as a 15% deviation in the tumor temperature was observed from the non-equilibrium state at 10.65 s exposure and 10 W power. Eventually, the calculation of the ablated volumes indicated that the volumes were up to 4.5 times larger by the Pennes model compared to the modified dual-phase-lag model. Conclusions: It can be concluded from the results that there should be a serious concern on the high intensity focused ultrasound modeling based on the parameters of blood vessels. Based on the thermal maps, the cancerous tissue should be exposed to a higher energy level of ultrasound waves in order to cause the desired damage against the estimated energy level predicted by the Pennes model. Graphical abstract: Image, graphical abstract